Do Suppliers Applaud Corporate Social Performance? - Zhang, Min (Journal of business ethics, 2014)
The influence of corporate social performance (CSP) on stakeholders is one of the focal issues in corporate social responsibility (CSR) research. Using data of listed companies in China, this paper examines whether CSR behavior in the form of charitable donations garners a positive reaction from suppliers. Results derived from both level and change model regressions show that superior CSP makes it easier for a firm to obtain trade credit from suppliers, although the effect is significant only in non-state-owned enterprises (non-SOEs). The results are robust to various measures of CSP and endogeneity tests. The results support the strategic philanthropy view and apply stakeholder theory in supply chain, that strategic CSR can help firms to attract suppliers and consolidate cooperative relationships with them, which in turn benefits the firms in terms of more trade credit financing from suppliers. This paper also shows that state-owned enterprises and non-SOEs have different CSR intentions and use CSR to achieve strategic goals in different ways. The conclusions drawn from this study provide practical guidance on CSR strategy, suggesting that CSR activities can help a firm in transition economies to enhance its corporate image, establish and consolidate the good relationship with suppliers, and obtain economic benefits or achieve long-term business objectives.